MEMBANGUN GENERASI JURNALISTIK: PELATIHAN PENULISAN BERITA DAN FOTOGRAFI MEDIA ONLINE UNTUK SISWA MADRASAH AN NASHAR MAKASSAR - Abd Majid; Siti Rahmawati; Muhammad Idris (As-Sidanah, 2025)
The target of this Community Partnership Program (PKM) is the students of Madrasah An Nashar in Makassar. Based on initial communications, several issues were identified: a lack of knowledge and awareness among students regarding journalistic photography, particularly in sports; limited education and exposure to photography; a scarcity of basic photography training in Makassar; and the absence of photography as a core subject in secondary schools. The training methods included lectures, demonstrations, Q &A sessions, and mentoring. The outcomes revealed a significant enhancement in participants' competitiveness, especially in journalistic and creative photography. During practical sessions, all participants were challenged to produce journalistic and creative photos aligned with the training theme, sharing their best work on social media platforms. Twenty active members of the student council attended the training, with full participation in demonstrations and practices, indicating the program's success. Evaluation through simulations and group assignments before and after the training assessed knowledge levels and responses to sports photography practices. The structured approach of delivering theoretical content prior to practical application proved effective, fostering independence and confidence among participants. The program's comprehensive execution, from preparation to field implementation, successfully engaged students in active learning.